How to find and overcome reason of the pain - an overview of the possible approaches in intracranial hypotension treatment - Hądzlik, Izabela; Piotrowski, Jan; Biały-Karbowniczek, Julia; Słychan, Katarzyna; Bulska, Klaudia; Brzozowska, Patrycja; Piela, Andrzej; Nowińska, Bianka; Łuczak, Blanka; Sławek, Konrad (Journal of Education, Health and Sport, 2024)
Intracranial hypotension syndrome develops following cerebrospinal fluid (CSF, cerebrospinal fluid) leakage as a result of iatrogenic or spontaneous interruption of the meninges. The main clinical manifestation of intracranial hypotension, whether spontaneous (SIH, spontaneous intracranial hypotension) or iatrogenic, is a chronic headache of the orthostatic type, which may be accompanied by symptoms of neurological deficits. Despite the usually benign course, subdural haematomas developing following SIH or cerebral venous sinus thrombosis can cause deterioration of the patient's condition and may even be life-threatening. An important role in the diagnosis of SIH is played by imaging studies (mainly magnetic resonance imaging) of the brain and spinal canal, sometimes supplemented by CSF pressure testing. If conservative treatment fails, consideration should be given to surgical management and epidural blood patch. SIH is dangerous, so it is important to know how to diagnose and treat it.